Awareness of European Otolaryngologists and General Practitioners Toward Laryngopharyngeal Reflux. (November 2019) - Lechien, Jerome R.; Mouawad, Francois; Mortuaire, Geoffrey; Remacle, Marc; Bobin, Francois; Huet, Kathy; Nacci, Andrea; Barillari, Maria Rosaria; Crevier-Buchman, Lise; Hans, Stéphane; Finck, Camille; Akst, Lee M.; et al.
Objectives: To investigate the current trends in management of laryngopharyngeal reflux (LPR) among young European otolaryngologists and general practitioners (GP). Methods: An international survey was sent to European general practitioners and all otolaryngologists under 45 years old from the 2017 IFOS meeting. This survey was conducted by the LPR Study Group of YO-IFOS (Young Otolaryngologists of the International Federation of Otolaryngological Societies). Results: Among the 2500 attendees, 230 European otolaryngologists (response rate = 9%) completed the survey; an additional 70 GPs also completed the survey. GPs did not differentiate between gastroeosophageal reflux disease (GERD) and LPR, overstating GERD-related symptoms (ie, heartburn and regurgitations) in LPR clinical presentation and relying on gastrointestinal endoscopy for LPR diagnosis. Otolaryngologists also believe that GERD-related symptoms are prevalent in LPR. Knowledge of nonacid and mixed LPR and use of multichannel intraluminal impedance-pH monitoring are still limited in both groups. A therapeutic dichotomy exists between groups: GPs mainly use a 4-week once daily empiric proton pump inhibitors (PPIs) trial, while otolaryngologists use PPIs twice daily for a longer therapeutic period ranging from 8 to 12 weeks. More than 50% of GPs and otolaryngologists believe that they are not adequately knowledgeable and skilled about LPR. Conclusion: The majority of GPs and otolaryngologists do not believe themselves to be sufficiently informed about LPR, leading to different practice patterns and grey areas. The elaboration of international recommendations in the management of reflux is needed to improve practices.